Hotness and pungent odour profiles of processed dried chilli (Capsicum annuum Linn. var Acuminatum Fingerh.) - Nitchara Toontom (Prince of Songkla University, 2015)
Thesis (Ph.D. (Food Science and Technology))--Prince of Songkla University, 2014